RETRACTED ARTICLE: A Complete Formula of Ocean Surface Absolute Geostrophic Current - Chu, Peter C. (Sci Rep, 2020)
Absolute geostrophic current at the ocean surface (S) contains three components: (1) absolute geostrophic current at the geoid undulation (N), (2) geostrophic shear (between S and N) due to horizontal gradient of dynamic ocean topography, and (3) geostrophic shear (between S and N) due to horizontal gradient of density. However, only the second component is used to represent the surface absolute geostrophic current in physical oceanography and satellite geodesy. Four public datasets are used to calculate each component. Evident difference between the surface absolute geostrophic current and the second component (i.e., geostrophic shear due to horizontal gradient of dynamic ocean topography) was found by the statistical characteristics with the relative root mean square difference of 0.605. It shows that the common practice in physical oceanography and satellite geodesy is not correct. The horizontal gradient of dynamic ocean topography alone cannot be claimed as the surface absolute geostrophic current.